PENGELOLAAN JENJANG KARIR DI RSUD I LAGALIGO WOTU KABUPATEN LUWU TIMUR PROVINSI SULAWESI SELATAN DALAM PERSPEKTIF EKONOMI ISLAM - hidayatullah, Hidayatullah; Purwanta, Purwanta; B, Endah Wening (LPPM Akademi Manajemen Administrasi Yogyakarta, 2023)
This study evaluates the implementation of career development at Rumah Sakit Umum Daerah I Lagaligo Wotu, East Luwu Regency, South Sulawesi, with a focus on optimal service to human resources. Career development involves education, training, promotion, and employee transfers, aiming to assess competence, enhance efficiency, and provide a foundation for professional development. Career advancement in the Islamic perspective is a concept that guides career development in alignment with ethical and moral values in Islam. In Islam, the career concept extends beyond professional achievements to include dedication and service to the community. The study utilizes a qualitative approach to understand the behavior, attitudes, motivation, and actions of the research subjects. It provides insights into career development efforts that can enhance the effectiveness of healthcare services and employee welfare at the hospital from the perspective of Islamic economics. The identified constraints include a lack of policy understanding and delays in the collection of promotion documents. Solutions involve improving employee task understanding, promoting positions through professional development, performance, and training.